Modelo de gestión administrativa para el fortalecimiento de la competitividad de la empresa "Macrotextil" - Araque, Andrea M. (2019)
The degree project which has been developed in this research proposes to design, an administrative management model for strengthening the competitiveness of the MACROTEXTIL company, with the aim of helping the business growth of this organization. Chapter I refers to the theoretical framework, which describes the technical terms in Administration - management, marketing - sales and operations - logistics, where the process is based, its characteristics and importance, strategies and the foundations of it, also He analyzed several concepts regarding the realization of the administrative management model and competitiveness. Chapter II, presents the methodology used in the work where an internal and external analysis was carried out to determine the strengths opportunities, weaknesses, threats and in this way diagnose the way of operating of said company. In chapter III, the development of the company's competitiveness management administrative model is presented, which proposes mission, vision, organizational structure, strategies and action plans, which lead the company to obtain a more favorable development in the market.